PENDEKATAN DINAS KESEHATAN DALAM PEMBERIAN PELAYANAN KESEHATAN DASAR MATERNAL PADA KOMUNITAS ADAT TERPENCIL SUKU ANAK DALAM DI KABUPATEN MERANGIN - Lailatul Khoiriyah; Retna Siwi Padmawati (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: Based on previous research in Sarolangun District which stated that mothers of Anak Dalam tribes do not want to come to give birth at the Health Service center provided by the government. Meanwhile in Merangin District, there were mothers of AnakDalam tribes who want to do ANC and gave birth to available health services.Objective: To explore the approach taken by the Merangin District Health Office in providing basic maternal health services tothe remote indigenous communities of the Anak Dalam tribe in the Merangin District area.Methods: This research was qualitative research with a single embedded case study design. The respondents were mothers,tumenggung (chief of tribe), health workers, holders of maternal health programs at the health department and the Head of HealthDistrict Office.Results: Maternal health services in Kabupaten Merangin included 14 services that cover the entire community including Anak Dalamtribe. Service delivery efforts were provided with a cultural approach and teamwork. The strategy of providing maternal health servicesto the Anak Dalam tribe was carried out with innovations in health care facilities thus the Anak Dalam tribe community begun to minglewith the community, understand maternal health, and finally accept maternal health services provided by health care facilities. Itwas also inseparable from cross-sectoral support in providing counselling and outreach about healthy life style of the Anak Dalam triberesidents. Therefore, the impact was Anak Dalam tribe begun to understand the importance and need to utilize health care facilitiesprovided by the government.Conclusion: The approach was carried out with cross-sectoral collaboration and initiation of innovation in health service facilities.Evaluation of the approach to providing health services can be viewed from the aspect of mistrust in health services and the acceptance of providing maternal health services to the Anak Dalam tribe.